Necrotizing E. coli pneumonia with subsequent pneumothorax in a dog: a case report - Vazin, Victoria Vida; Huebner, Sara; Deforge, Teagan; Wood, Michael; Mitropoulou, Athanasia (Frontiers in Veterinary Science, 2025)
Necrotizing pneumonia is a poorly described and rarely reported phenomenon in veterinary medicine. The objective of this case report is to describe the successful management of a case of necrotizing pneumonia in a dog requiring medical and surgical management. This case describes a 9-year-old male neutered Siberian Husky mix that presented to an emergency center for a chronic cough not responsive to antibiotics including doxycycline and amoxicillin—clavulanate. Diagnostic imaging studies were consistent with severe multilobular pneumonia, pleural effusion and secondary pneumothorax. Aerobic culture of a bronchoalveolar lavage sample isolated Escherichia coli that was susceptible to enrofloxacin. A median sternotomy was performed when antibiotics alone were unable to fully clear the infection and the cranial segment of the left cranial lung lobe was removed. Histopathology of this lung lobe indicated subacute suppurative and fibrinohemorrhagic bronchopneumonia with parenchymal and pleural necrosis. The dog survived to discharge with resolution of pneumonia based on thoracic radiographs after 38 days. Necrotizing pneumonia can potentially be adequately treated with appropriate escalation of medical and surgical management.